Analisis Resource-Based View dan Lifestyle Segmentation pada Perusahaan Sociopreneurship: Studi Kasus CV. Agradaya - Asa Shaliha Rahmaningrum; Yosua Febro Gunawan Peranginangin; Siti Rahma; Sekar Ayu Putri Permana (Universitas Muhammadiyah Surakarta, 2024)
The changes in lifestyle which will eventually happen along with the advancement of technology and global phenomenon requires business to adapt and contribute to the well-being of the society despite its main goal to earn profit. This research seeks to give understanding how entrepreneurship which is built upon empowerment of a community could survive, even taking an important part in the competition. This research uses a qualitative method and case study approach with primary data gotten from an interview and secondary data available on the internet. The observation of one of social entrepreneurships in Yogyakarta indicates that such business gives direct positive impacts to the local community and the environment around it.